4‐bit Multilevel Operation in Overshoot Suppressed Al2O3/TiOx Resistive Random‐Access Memory Crossbar Array. (26th May 2022) - Kim, Sungjoon; Park, Jinwoo; Kim, Tae-Hyeon; Hong, Kyungho; Hwang, Yeongjin; Park, Byung-Gook; Kim, Hyungjin
Abstract : To apply resistive random‐access memory (RRAM) to the neuromorphic system and improve performance, each cell in the array should be able to operate independently by reducing device variation. In addition, it is necessary to lower the operating current of the RRAM cell and enable gradual switching characteristics to mimic the low‐energy operations of biological. In most filamentary RRAMs, however, overshoot current occurs in the forming stage, and the RRAM shows large device variation, high operating current, and abrupt set and reset switching characteristics. Herein, the shortcomings occurring in the forming stage are overcome by introducing and optimizing an overshoot suppression layer. Consequently, the RRAM exhibits gradual switching characteristics both in the set and reset regions, thereby enabling implementation of 4‐bit multilevel operation. In addition, the forming step can be easily performed in a 16 × 16 crossbar array owing to its self‐compliance characteristics without disturbing neighboring cells in the array. The tuning and vector–matrix multiplication (VMM) operations are also experimentally verified in the array. Finally, classification performance with off‐chip training is compared in terms of accuracy and robustness to tuning tolerance depending on the number of bits of the implemented multiconductance levels. Abstract : Al2 O3 /TiO x based resistive switching devices with overshoot suppressed layer (OSL) are integrated in 16 × 16 crossbar array. Especially, tuning operation of 4‐bit states is demonstrated with incremental pulse programming and verifying scheme for off‐chip training of neuromorphic system. OSL effectively removes overshoot during the forming stage and enables gradual switching characteristics through weak filaments.